2008
DOI: 10.2214/ajr.07.3372
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of 18F-FDG PET/CT in Detecting Pelvic and Paraaortic Lymph Node Metastasis in Patients with Endometrial Cancer

Abstract: Integrated FDG PET/CT is superior to conventional imaging techniques, but it is only moderately sensitive in predicting lymph node metastasis preoperatively in patients with endometrial cancer. Even PET/CT should not replace lymphadenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(81 citation statements)
references
References 27 publications
3
75
2
1
Order By: Relevance
“…It is important to know or predict the stage of disease before the operation to perform full staging surgery. In previous studies, it was found that PET/CT has moderate sensitivity and high specificity for detecting nodal metastasis (29)(30)(31) and high sensitivity and specificy for detecting metastatic disease (32). Authors concluded that PET/CT is not a substitute for lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to know or predict the stage of disease before the operation to perform full staging surgery. In previous studies, it was found that PET/CT has moderate sensitivity and high specificity for detecting nodal metastasis (29)(30)(31) and high sensitivity and specificy for detecting metastatic disease (32). Authors concluded that PET/CT is not a substitute for lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, LNs with no detectable tracer uptake were deemed negative for metastatic spread, even if their short-axis diameter was larger than 1 cm. Semiquantitative analysis to determine a standardized value for FDG uptake in the nodal lesions was not performed in our series, in line with the PET/CT image analysis method of several other studies [26][27][28][29][30][31] .…”
Section: Image Analysismentioning
confidence: 99%
“…There have been several reports demonstrating the accuracy of FDG-PET/CT for detecting LN metastasis in uterine cancer [20,[26][27][28][29][30][31] . They revealed the sensitivity, specificity, and accuracy of PET/CT on region-specific analyses were 36%-72%, 88%-99% and 84%-99%, respectively, and that corresponding values for patient-based analyses were 41%-77%, 56%-100% and 76%-89%.…”
Section: Specificity Accuracymentioning
confidence: 99%
See 2 more Smart Citations